Wild about weeds : garden design with rebel plants - Wallington, Jack (Laurence King Publishing, 2019)
"Not all weeds are ugly uncontrollable brutes. Yes, they can be difficult and intimidating, but by learning how to grow weeds in unexpected ways you will become a better gardener with a more interesting garden. This book profiles over 50 weeds and shows you surprising ways to grow them, no matter what your garden type: from borders to boxes, sunny to shady, poor soil to rich, tropical to formal, Japanese-style to prairies. With interviews, tips and advice from celebrated gardeners, learn how to let weeds flourish without taking control. Wild about Weeds is the must-have guide for modern gardeners that explains how to tame and nurture the most challenging of plants."